HUBUNGAN KUALITAS PELAYANAN DENGAN KEPUASAN NASABAH PT BANK NEGARA INDONESIA (PERSERO) TBK KANTOR CABANG PEMBANTU PANGERAN ANTASARI BANJARMASIN - Mohdari Mohdari (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2018)
Abstract, The purpose of this study was to analyze the service relationship with customer satisfaction of PT Bank Negara Indonesia (Persero) Tbk Pangeran Antasari Banjarmasin Branch Office (KCP). The method used in this research is analytical method, with a sample of 100 people, the sampling method uses Accidental Sampling. The results of the analysis using multiple logistic regression obtained p value 0.000 < 0.05 so it can be concluded that there is a relationship between service quality and customer satisfaction at PT BNI's branch office Pangeran Antasari Banjarmasin